1999
DOI: 10.4031/mtsj.33.2.8
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Bycatch Reduction Technology in the Southeastern United States Shrimp Fishery

Abstract: Shrimp trawl bycatch is a significant source of fishery induced mortality for managed species including red snapper (Lutjanus campechanus Poey), Spanish mackerel (Scomberomorus maculatus MitcheU), and weakfish (Cynoscion regalis Baloch, Schneider) in the southeastern United States. These species have been overfished and are under both state and federal management plans which include regulations mandating reduction of shrimp trawl bycatch mortality. In 1990 the U.S. Congress passed amendments to the Magnuson F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
1
19
0
4
Order By: Relevance
“…Fisheye BRDs (Watson et al, 1999) were allowed in 2001-2002, but were banned in 2003 because they were much less effective than soft-panel and rigid-grate BRDs, which are the only types now allowed (Figs. 1-3).…”
Section: Types Of Brds Evaluatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Fisheye BRDs (Watson et al, 1999) were allowed in 2001-2002, but were banned in 2003 because they were much less effective than soft-panel and rigid-grate BRDs, which are the only types now allowed (Figs. 1-3).…”
Section: Types Of Brds Evaluatedmentioning
confidence: 99%
“…Research experiments on bycatch reduction devices (BRDs) have shown many types to be effective at reducing the bycatch of fishes in shrimp and prawn trawls (Isaksen et al, 1992;Broadhurst, 2000;Watson et al, 1999). However, few have been quantitatively evaluated after adoption to determine what level of bycatch reduction was achieved in the fishery.…”
Section: Introductionmentioning
confidence: 97%
“…Briefly, according to Watson et al (1986), soft panel separator gear for trawls, designed originally for cold-water shrimp fisheries in the 1960s, were the first turtle excluder gear evaluated for the shrimp fishery. Testing and development in commercial fishing conditions in the Gulf of Mexico indicated a rigid grid was needed due to the diversity in the sizes and types of fish bycatch that clogged or ripped soft panels (Watson and McVea 1977). Oravetz and Grant (1986) describe the adaptation of the "jellyball" shooter, a hooped grid with a slit at the top inserted by Georgia shrimp fishermen ahead of the cod end of the trawl to exclude jellyfish.…”
Section: Reinitiation Of Consultationmentioning
confidence: 99%
“…a narrow selection range (SR; the di erence in length between the 25 and 75% capture probabilities), is preferred. Rigid sorting grids were rst introduced into shrimp trawl sheries to reduce the by-catch of turtles (Watson and McVea, 1977) and juvenile sh (Isaksen et al, 1992). Grids were later modi ed to perform as size selective devices (Larsen and Isaksen, 1993) and a large number of size selective grid designs have been tested in a variety of sheries (Anon, 1998).…”
Section: Introductionmentioning
confidence: 99%